2012
DOI: 10.1126/scitranslmed.3003041
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induction of Osteopontin (SPP1) Mediates T H 17 Inflammation in Human and Experimental Emphysema

Abstract: Smoking-related lung diseases are among the leading causes of death worldwide, underscoring the need to understand their pathogenesis and develop new effective therapies. We have shown that CD1a+ antigen-presenting cells (APCs) from lungs of patients with emphysema can induce autoreactive T helper 1 (TH1) and TH17 cells. Similarly, the canonical cytokines interferon-γ (IFN-γ) and interleukin-17A (IL-17A) are specifically linked to lung destruction in smokers, but how smoke activates APCs to mediate emphysema r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
155
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(176 citation statements)
references
References 45 publications
15
155
1
1
Order By: Relevance
“…Therefore, since the distribution of TCR can vary according to age and genetic factors, the correlation between PCB and TCR found in our exposed workers seems to indicate a stimulation of the specific expression of TCR a-~involved in lymphocyte antigen recognition (23). On the contrary, the results of the study seem to exclude a direct effect of smoke and alcohol on TCR a-~and y-8 cells , in contrast with findings of some authors reporting an effect of smoke on TCR y-8 cells in humans and in mice (23,24). More intriguing and original, in PCB exposed subjects, is the relative % reduction of TCR y-8 T cells, in human particularly present in epithelia, both in the peripheral blood on the number of cigarettes smoked per day confirms the immunomodulating action of tobacco smoking that has already been reported by other authors, who found a greater and significant increase of Treg in bronchial alveolar lavage (BAL) of healthy smokers as compared to non-smokers/ex-smokers/smokers with chronic obstructive pulmonary disease (COPD) (9,10,30).…”
Section: Discussioncontrasting
confidence: 96%
“…Therefore, since the distribution of TCR can vary according to age and genetic factors, the correlation between PCB and TCR found in our exposed workers seems to indicate a stimulation of the specific expression of TCR a-~involved in lymphocyte antigen recognition (23). On the contrary, the results of the study seem to exclude a direct effect of smoke and alcohol on TCR a-~and y-8 cells , in contrast with findings of some authors reporting an effect of smoke on TCR y-8 cells in humans and in mice (23,24). More intriguing and original, in PCB exposed subjects, is the relative % reduction of TCR y-8 T cells, in human particularly present in epithelia, both in the peripheral blood on the number of cigarettes smoked per day confirms the immunomodulating action of tobacco smoking that has already been reported by other authors, who found a greater and significant increase of Treg in bronchial alveolar lavage (BAL) of healthy smokers as compared to non-smokers/ex-smokers/smokers with chronic obstructive pulmonary disease (COPD) (9,10,30).…”
Section: Discussioncontrasting
confidence: 96%
“…However, IL-17 has been associated with certain forms of severe asthma (34), CF (40), and chronic obstructive pulmonary disease (44), and in these chronic lung diseases IL-17 may contribute to pathology. The role of IL-22 and IL-22-binding protein in these diseases needs to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports unraveled beneficial effects of SFN in experimental chronic obstructive pulmonary disease (COPD) (28,53). SFN reduced pulmonary inflammation in COPD, a condition associated with Th17 responses (54,55). The aim of our study was to elucidate the immunoregulatory capabilities of SFN in terms of affected immune cells and underlying molecular mechanisms during T cell-mediated autoimmune responses.…”
Section: Sfn Treatment Inhibits Il23a/il12b Expression and Th17/th1 Dmentioning
confidence: 99%